Analisis Yuridis Efektivitas Hong Kong International Arbitration Centre Sebagai Mekanisme Alternatif Penyelesaian Sengketa - Tanjung, Salsas Bila Juniyanti; Amelia, Dean Putri; Ramadhan, Aditya Rizky; Alvito, Haykal Rizki; Abdul, Rizki Rivandi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Hong Kong International Arbitration Centre is an urgent study in the context of the Out-of-Court Dispute Resolution course, because it represents the practice of implementing international arbitration that meets the principles of fairness, speed, efficiency, and accountability. The study of HKIAC also reflects a paradigm shift in the legal world, from the dominance of litigation to alternative dispute resolution that is more adaptive to the dynamics of global business. The study in this study covers the working mechanism of HKIAC in handling international arbitration and the dispute resolution procedures at HKIAC as well as the requirements that must be met by the parties. This study uses a qualitative research method, namely an approach that focuses on understanding the phenomenon of the dispute resolution process, including the appointment of arbitrators, handling case administration, and ensuring compliance with arbitration rules. The results of the study are that the existence and role of HKIAC are very important not only in the context of resolving international business disputes, but also as a symbol of the transition from the dominance of the litigation system to a more progressive non-litigative dispute resolution system. With all these characteristics, HKIAC can be considered as a modern institutional arbitration institution that responds to the needs of global trade and the dynamics of the international business world with a professional, adaptive and trustworthy approach